Effects of the Blp1 locus, which controls melanin accumulation in the barley ear, on the size and weight of seeds - O. Y. Shoeva; A. Y. Glagoleva; T. V. Kukoeva (Труды по прикладной ботанике, генетике и селекции)
Background. In cereals, photosynthetically active parts of the ear significantly contribute to seed size and weight at the grain-filling stage. In barley, ear tissues may accumulate melanin pigments synthesized in chloroplast-derived melanoplasts. Effects of such pigments on yield parameters of seeds have not been evaluated to date.Materials and methods. Seed weight and size assessed by image analysis were compared between two near-isogenic barley lines differing in alleles of the Blp1 gene, which determines melanin accumulation in ear tissues. Data on grainrelated parameters were collected during 6 years and include data on seeds grown either in the field or under greenhouse conditions.Results and discussion. A negative effect of the Blp1 locus on the weight of 1000 seeds harvested in the field but not in the greenhouse was revealed. To determine whether this effect is related to grain size, a comparison of two-dimensional linear parameters of seeds between the lines was performed. It was shown that unlike the length and the area of seeds, the width of seeds was also negatively affected by the Blp1 locus. Although the same factors affected the weight of 1000 seeds and the width of seeds, a correlation between them was not found, implying a dependence of seed weight on other factors such as thickness and its related parameter, seed volume.Conclusion. Effects of barely ear pigmentation and of the gene controlling it on yield-related parameters of seeds were studied here for the first time. The observed negative impact of the Blp1 locus on seed weight and size may be mediated by an interfering chloroplast activity and/or accumulation of assimilates via melanogenesis. Additional studies are necessary to test this supposition and to investigate the interaction of melanin synthesis and photosynthetic activity of the tissues accumulating this pigment.